Design of Multi-function Network of Coal Mine Underground - WANG Wu-yi (Gong-kuang zidonghua, 2010)
In view of problem that each production automation system of coal enterprises has its own system, the paper proposed a design scheme of three-network convergence of control network, video network and audio network based on high-speed fiber network covering production automation system of whole mine. It introduced implementation of the scheme in Donghuantuo Coal Mine of Kailun Group in details, namely wiring method of underground ring network and surface ring network and access method of each production automation system. The actual application showed that the scheme realizes to build unified coal mine communication network with structure of double-ring, double-network and double-redundancy.